DIGITAL HR TRANSFORMATION AND ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM TECHNOLOGY-DRIVEN FIRMS - Anita Kusuma Dewi; Noerismayanti Noerismayanti; Nur Ratnasari (INJOSEDU: International Journal of Social and Education, 2026)
Digital transformation in human resource management has become a crucial strategy for technology-based companies to improve organizational effectiveness and business competitiveness. This study aims to analyze the impact of digital HR transformation on organizational performance in technology-oriented companies through a literature review approach. The research method used is a literature study by reviewing various scientific articles, international journals, research reports, and relevant academic sources that discuss digital HR transformation and organizational performance in the context of modern companies. The results of the study indicate that the implementation of digital technology in HR functions, such as the use of artificial intelligence, big data analytics, cloud-based HR systems, and automated recruitment, can improve operational efficiency, employee productivity, decision-making quality, and organizational flexibility in facing business changes. In addition, digital HR transformation also contributes to increased employee engagement, the development of digital competencies, and the acceleration of organizational innovation. However, several challenges remain, including resistance to change, limited digital competency of human resources, and issues of data security and privacy. This study concludes that digital HR transformation plays a strategic role in driving organizational performance improvement in technology-based companies when supported by adaptive leadership, an innovative organizational culture, and adequate technological readiness. This research is expected to serve as an academic and practical reference for organizations in designing sustainable digital-based HR management strategies.